Long-Term Efficacy and Variability of Converting Nitrate in Beetroot Juice to Plasma Nitrite. (29th May 2020) - Miller, Gary; Collins, Summer
Abstract: Objectives: Acute consumption of beetroot juice has cardiovascular benefits and improves exercise performance. Beetroot juice contains high concentrations of dietary nitrate (NO3 − ). Consumed NO3 − is absorbed and reduced to nitrite (NO2 − ) through an enterosalivary pathway by oral facultative anaerobic bacteria. The absorbed NO2 − is reduced to nitric oxide (NO) by a nitric oxide synthase independent pathway. Due to the heterogeneous efficiency of converting NO3 − to NO2 −, if beetroot juice is to be used to improve health, it is necessary to understand the variability and efficacy of long-term beetroot juice supplementation on converting dietary NO3 − to plasma NO2 − . Methods: Healthy nonsmoking adults (mean age = 56.0 5.1 years) were randomized to consume beetroot juice daily with either 400 mg NO3 − (BRJ+; n = 6; 4 females) or without NO3 − (Placebo; n = 7; 6 females) for 12 weeks. They were instructed to refrain from consuming high nitrate containing foods and avoid using mouthwash for the study duration. At baseline prior to randomization, plasma levels of NO3 − and NO2 − were measured following an overnight fast before (pre) and 90 minutes after (post) consuming a 400 mg dose of BRJ+ to calculate % change [(post-pre)/pre * 100]. % change in plasma NO3 − and NO2 − was measured at weeks 1, 2, 3, 4, 8, and 12. Results: At baseline, 1 out of 13 participants was defined as a non-responder (< 100% increase in %change of plasma NO2 − after a NO3 − dose). Weekly group means of %change in plasma NO2 − for BRJ + varied from 400% at week 1 to 140% at week 12. Week-to-week individual variation in % change of plasma NO2 − for BRJ + ranged from a 7.4% decrease to a 1324% increase. The BRJ + group had significantly greater nitrate and nitrite variability ( P < 0.05) compared to placebo. As expected, % change for plasma NO3 − ( P < 0.001) and NO2 − ( P = 0.001) was greater for the BRJ + vs. placebo at all post-randomization time points. Conclusions: Long-term consumption of NO3 − containing beetroot juice increased plasma NO2 − throughout the 12 week study. However, the large variability in response between individuals and across time needs further investigation to understand factors that influence this variability. Funding Sources: Translational Science Center, Wake Forest University.